2023
DOI: 10.3389/fimmu.2022.1047986
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional alteration of CD45+ immune cells in the decidua of preeclampsia patients analyzed by mass cytometry (CyTOF)

Abstract: Preeclampsia (PE) is a severe placenta-related pregnancy disease that has been associated with maternal systemic inflammation and immune system disorders. However, the distribution and functional changes in immune cells of the maternal–placental interface have not been well characterized. Herein, cytometry by time-of-flight mass spectrometry (CyTOF) was used to investigate the immune atlas at the decidua, which was obtained from four PE patients and four healthy controls. Six superclusters were identified, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A paper published in 2022 presents the results of the study, which showed an increased level of expression of OX40 and CXCR5 on decidual immune cells in the course of pre-eclampsia compared to physiological pregnancy [82]. The authors of the publication em-phasized the role of OX40 and CXCR5 overexpression in the production of autoantibodies by B lymphocytes, which is one of the components of the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…A paper published in 2022 presents the results of the study, which showed an increased level of expression of OX40 and CXCR5 on decidual immune cells in the course of pre-eclampsia compared to physiological pregnancy [82]. The authors of the publication em-phasized the role of OX40 and CXCR5 overexpression in the production of autoantibodies by B lymphocytes, which is one of the components of the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…This affects disease manifestations and treatment. [ 5 ] During pregnancy the mucous membrane of the upper respiratory tract becomes thickened, mildly congested, and edematous, influenced by elevated levels of estrogen and progesterone, predisposing pregnant women to upper respiratory tract infections. [ 6 ] The inflammatory response to viral respiratory infections in pregnant women is notably heightened.…”
Section: Introductionmentioning
confidence: 99%